2005
DOI: 10.1080/02652030500077502
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure assessment of infants to bisphenol A from the use of polycarbonate baby milk bottles

Abstract: The residual bisphenol A (BPA) levels in 28 different brands of polycarbonate (PC) baby milk bottles available in the Singapore market were measured. With a detection limit of 3 mg/kg, BPA residues were detected in 19 out of the 28 PC baby milk bottles at levels between 4.01 and 141 mg/kg, with a mean of 28.1 +/- 31.4 mg/kg and a median of 17.2 mg/kg. The potential migration of BPA from each of the 28 PC milk bottles was also measured using food-simulating solvents and time conditions recommended by the US Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…BPA has been detected in human breast milk [20,21], polycarbonate baby bottles [60], and in some infant formulas, likely due to the packaging materials used [61,62]. Average exposure of bottle-fed newborns to BPA was estimated at 24 μg/kg BW/day, and 15 μg/kg BW/day for infants at 3 months of age [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPA has been detected in human breast milk [20,21], polycarbonate baby bottles [60], and in some infant formulas, likely due to the packaging materials used [61,62]. Average exposure of bottle-fed newborns to BPA was estimated at 24 μg/kg BW/day, and 15 μg/kg BW/day for infants at 3 months of age [60].…”
Section: Discussionmentioning
confidence: 99%
“…BPA has been detected in human breast milk [20,21], polycarbonate baby bottles [60], and in some infant formulas, likely due to the packaging materials used [61,62]. Average exposure of bottle-fed newborns to BPA was estimated at 24 μg/kg BW/day, and 15 μg/kg BW/day for infants at 3 months of age [60]. Human infants produce glucuronidases in their digestive tracts with increased production until adult levels are reached at four years of age [63] suggesting that conjugated BPA may be deconjugated and activated during the digestion process.…”
Section: Discussionmentioning
confidence: 99%
“…60 Exposure to BPA in the human fetus occurs through maternal exposure, and in the neonate through ingestion of maternal milk, tinned food and infant formula. 6163 …”
Section: Edcs and Neoplasia In Femalesmentioning
confidence: 99%
“…High temperatures as well as acidic and alkali solutions cause polymer degradation via hydrolysis, resulting in increased BPA migration. After incubation for 8, 72, and 240 hr in food-simulating solvents (10% ethanol at 70°C and corn oil at 100°C), mean BPA migration increased with incubation time (Onn Wong et al 2005). After a sequence of washing and rinsing, Le et al (2008) found that new poly-carbonate bottles leached 1.0 ± 0.3 μg/mL BPA (mean ± SD) into the bottle content after incubation at room temperature for 7 days.…”
mentioning
confidence: 99%